Konflik Kepentingan Struktural dalam Perjanjian Kerja Sama Notaris Rekanan Bank: Perspektif Prinsip Netralitas Berdasarkan Undang-Undang Jabatan Notaris - Thertia Maulidya (Legalita, 2026)
This study examines violations of the principle of notarial neutrality in the implementation of cooperation agreements between partner Notaries and banks, reviewed in light of Law Number 2 of 2014 concerning the Office of Notary. The practice of partnership agreements between Notaries and banks has developed rapidly within Indonesia’s banking system; however, it raises legal issues related to the independence and neutrality of Notaries as public officials. This research employs a normative juridical method with statutory, conceptual, case-based, and analytical approaches to examine the conflict between clauses contained in cooperation agreements and the applicable legal provisions. The findings indicate that such partnership agreements contain problematic clauses, including obligations to prioritize the interests of the bank, prohibitions on providing legal advice to debtors, and commission-based honorarium systems, all of which clearly contradict Article 16 paragraph (1) letters a and d of the Notary Law. These contradictions result in legal consequences in the form of the degradation of the evidentiary strength of the notarial deed into a private deed or its nullification by operation of law as stipulated in Article 84, as well as opening the possibility of claims for damages and administrative sanctions against the Notary. This study concludes that partnership practices which disregard the principle of neutrality have created a structural conflict of interest that threatens the integrity of the notarial profession and legal certainty for the public.